Membangun Integritas Notaris Dari Penyalahgunaan Kewenangan - Afrilia Era Vazira; Citra Bethari Ratih; Nayla Oktri Ramadhani; Nina Handayani; Baidhowi . (GLOBAL SCIENTS PUBLISHER, 2026)
This article discusses the urgency of developing notary integrity as a preventive effort against abuse of authority in notary practice in Indonesia. Notaries as public officials have a strategic role in ensuring certainty and legal protection through authentic deeds, so that integrity is the main foundation in the implementation of their positions. The results of the discussion showed that there were various patterns of abuse of authority, including procedural irregularities, manipulation of the substance of the deed, conflicts of interest, and collusion that had an impact on legal losses for the parties. These irregularities have administrative, civil, criminal, and ethical consequences. To overcome this, a comprehensive strategy is needed through strengthening professional ethics, increasing supervision, transparency, and building a legal culture with integrity. Thus, notary integrity is the key to maintaining professionalism, accountability, and public trust in notary institutions.